2017
DOI: 10.1038/srep45845
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of induction chemotherapy followed by chemoradiotherapy in patients with borderline resectable and unresectable locally advanced pancreatic cancer

Abstract: There is not a clear consensus regarding the optimal treatment of locally advanced pancreatic disease. There is a potential role for neoadjuvant therapy to treat micrometastatic disease with chemotherapy, as well as for the treatment of local disease with radiotherapy. We evaluated the safety and efficacy of induction chemotherapy with oxaliplatin and gemcitabine followed by a high weekly dose of gemcitabine concurrent to radiation therapy in patients with borderline resectable and unresectable locally advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Surgical resection represents the optimal treatment for patients affected by PDAC (2,3). Unfortunately, due to the advanced stage of the disease at first diagnosis, mostly related to the presence of distant metastases or local vascular invasion, only a minority of PDAC patients are eligible for upfront surgery (4).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection represents the optimal treatment for patients affected by PDAC (2,3). Unfortunately, due to the advanced stage of the disease at first diagnosis, mostly related to the presence of distant metastases or local vascular invasion, only a minority of PDAC patients are eligible for upfront surgery (4).…”
Section: Introductionmentioning
confidence: 99%
“…In a phase-I/II dose escalation trial Ben-Josef and colleagues reported a median overall survival time of 14.8 months with most patients of the study receiving 55 Gy prescribed dose [18]. Another Phase-II study with induction chemotherapy followed by radiochemotherapy up to 59.4 Gy total radiation dose reported a median overall survival time of 14 months in unresectable patients [19]. Despite further dose escalation, permanent local tumor control is still unsatisfactory with in-field recurrences in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, several studies that evaluated neoadjuvant approaches have since challenged this convention, showing conversion to resectability and similar outcomes to upfront resectable PDAC. [41][42][43][44] A 2019 meta-analysis involving 313 patients with borderline resectable pancreatic cancer who received FOLFIRINOX (24 studies: 16 retrospective and 8 prospective) reported a median OS of 22.2 months. 45 Imaging after neoadjuvant treatment will not always show a radiographic response.…”
Section: Borderline Resectable Diseasementioning
confidence: 99%